Examining pathways linking rural labour outflows to the abandonment of arable land in China. Issue 1 (13th October 2021) - Chen, Lili; Meadows, Michael E.; Liu, Ye; Lin, Yanliu
Abstract: Against the backdrop of increasing rural labour outflow in China, the marginalisation of agriculture and arable land abandonment has become prevalent. Previous studies have examined the linkages between rural labour outflow and arable land at the national scale but have largely ignored regional differences. Moreover, mechanisms linking rural labour outflow to abandonment have not been analysed systematically. This study uses 2016 China Labour‐force Dynamics Survey data (CLDS) and structural equation models (SEMs) to examine the means by which rural labour outflows affect arable land abandonment regionally. The analysis focuses on the mediating role and the moderating role of land tenure approval (LTA), nonagricultural income (NAI), agricultural mechanisation (AMC), and agricultural production efficiency (APE). There are three major findings. Firstly, in the main grain‐producing areas (MGPA), part‐time labour outflow alone is positively associated with arable land abandonment, while in the main grain‐consuming areas (MGCA), only off‐farm labour is directly related; there is no significant relationship between labour outflow and arable land abandonment in grain production and marketing balance areas (GPMBA). Secondly, part‐time labour does not necessarily lead to reduced levels of mechanisation, although lower APE emerges as an important factor in promoting arable land abandonment. Thirdly, the relationships between off‐farm labour/part‐time labour and arable land abandonment are moderated by LTA in both MGPA and GPMBA, while the moderation effect exists only in the case of part‐time labour in MGCA and GPMBA. We conclude that policies and measures in relation to agriculture and abandonment should be formulated differently for different regions.